2018
DOI: 10.1002/ptr.6169
|View full text |Cite
|
Sign up to set email alerts
|

Nigella sativa extract is a potent therapeutic agent for renal inflammation, apoptosis, and oxidative stress in a rat model of unilateral ureteral obstruction

Abstract: Unilateral ureteral obstruction (UUO) is a well-established experimental model to evaluate renal interstitial fibrosis. Current study is aimed to investigate the effects of Nigella sativa (NS) extract and renin-angiotensin system (RAS) blockade against kidney damage following UUO in rats. In this study, the rats received intraperitoneal injection of losartan (15 mg/kg), captopril (30 mg/kg), and two doses of NS extract (200 and 400 mg/kg) for 18 consecutive days. At the fourth day of the experiment, laparotomy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 30 publications
4
22
0
Order By: Relevance
“…Interestingly, on the basis of our results, downregulation of these fibrogenic markers by TQ was more pronounced than of the effects of losartan and captopril indicating the RAS inhibitory effects of TQ. In agreement with these observations, in our recent studies, we found that NS extract and TQ downregulate ANG II expression in the kidneys with ureteral obstruction (Hosseinian et al, ; Hosseinian, Ebrahimzadeh Bideskan, et al, ). Moreover, as shown by immunohistochemical assessments, Masson's trichrome staining also showed that TQ effectively decreases the ECM accumulation in UUO rats.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Interestingly, on the basis of our results, downregulation of these fibrogenic markers by TQ was more pronounced than of the effects of losartan and captopril indicating the RAS inhibitory effects of TQ. In agreement with these observations, in our recent studies, we found that NS extract and TQ downregulate ANG II expression in the kidneys with ureteral obstruction (Hosseinian et al, ; Hosseinian, Ebrahimzadeh Bideskan, et al, ). Moreover, as shown by immunohistochemical assessments, Masson's trichrome staining also showed that TQ effectively decreases the ECM accumulation in UUO rats.…”
Section: Discussionsupporting
confidence: 85%
“…The animals were randomly divided into five groups ( n = 8 in each), as follows: Sham‐operated group : Normal saline was intraperitoneally (ip) injected (0.3 ml) for 18 days, and laparotomy without ureteral ligation was performed on the fourth day of the experiment. UUO group : Normal saline was injected (0.3 ml, ip) for 18 days, and laparotomy and ligation of the left ureter were performed on the fourth day of the experiment. Los + UUO group : Losartan was injected (0.3 ml equal to 15 mg/kg, ip; Manucha, Carrizo, Ruete, Molin, & Valles, ; Radović et al, ) daily for 18 days, and laparotomy and ligation of the left ureter were performed on the fourth day of the experiment. Cap + UUO group : Captopril was injected (0.3 ml equal to 30 mg/kg; Larivière et al, ; Hosseinian, Ebrahimzadeh Bideskan, et al, ) for 18 days, and laparotomy and ligation of the left ureter were performed on the fourth day of the experiment. TQ + UUO group : TQ was injected (0.3 ml equal to 10 mg/kg; Hosseini et al, ) for 18 days, and laparotomy and ligation of the left ureter were performed on the fourth day of the experiment. …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Alternatively, thymoquinone has an antioxidant effect, cleans free radicals and superoxide anions, and inhibits cyclooxygenase and 5‐lipoxygenase pathways, so it inhibits the inflammatory process (Khan & Thamilselvan, ). Moreover, multiple in vivo and in vitro studies have showed that high levels of oxalate may have a toxic effect on renal epithelium through the intracellular oxidative stress process (Hosseinian, Ebrahimzadeh Bideskan, Shafei, Sadeghnia, & Soukhtanloo, ). Hence, black seed treatment may protect against the changes associated with oxidative stress and oxidative damage associated with lithogenesis (Bashir et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Its antioxidant feature which prevents oxidative damage has been proved in several studies (11,12,14,15,16). This study aimed to histopathologically investigate the protective effects of NSO administered i.p.…”
Section: Introductionmentioning
confidence: 99%